Risk factors and clinical features associated with death at the COVID-19 isolation ward of Clairwood Hospital/KwaZulu-Natal, South Africa: A retrospective case-control study. - Riziki Ghislain Manimani; Tambwe Willy Muzumbukilwa; Wilbroda Hlolisile Chiya; Furaha Bashengezi Esther; Benjamin Muthambi; Nombulelo Magula (Journal of Public Health and Development, 2026)
The COVID-19 pandemic posed significant challenges to healthcare systems worldwide. This study aimed to investigate the risk factors associated with death among patients admitted directly to the COVID-19 isolation ward at Clairwood Hospital. A case-control study was undertaken, involving a total of 400 study participants divided equally into 200 cases (deaths) and 200 controls (survivors). Data were collected retrospectively from medical records and analysed using Chi-square tests, univariate, and multivariate logistic regression. The patients had a mean age of 54.1 years (SD=18.9), with 217(54.2%) being female. A respiratory rate exceeding 20 breaths per minute was documented in 177 patients (44.2%), a heart rate greater than 100 beats per minute in 99 patients (24.7%), and a SpO₂ level below 85% on room air in 79 patients (19.7%). Cough was the most common symptom, occurring in 239 (59.7%) patients, while hypertension was the most prevalent comorbidity, present in 157 (39.2%) patients at the time of admission. Chi-square test analyses demonstrated statistically significant associations between mortality and age, fever, cough, shortness of breath, hypertension, diabetes, chronic kidney disease (CKD), obesity, respiratory rate, heart rate, and oxygen saturation (SpO₂) (all p < 0.05). On multivariate analysis, increasing age (adjusted odds ratio [aOR]: > 60 years: 12.27 [95% CI: 1.27–118.44]), fever (aOR: 2.86 [95% CI: 1.29–6.31]), shortness of breath (aOR: 9.86 [95% CI: 5.64–17.24]), hypertension (aOR: 2.07 [95% CI: 1.05–4.11]), obesity (aOR: 4.68 [95% CI: 1.43–15.28]), were associated with increased odds of death among COVID-19 patients at admission. No statistically significant associations were observed for other variables after adjustment. Proactive measures to identify and manage these risk factors are crucial in reducing mortality rates and enhancing the overall care of COVID-19 patients in isolation wards.